Theoretical Basis for Digital Economy Development – Implications for Vietnam - Vo, Xuận Vinh; Nguyen , Phong Nguyên; Tran, Đăng Khoa; Tran, Thị Thanh Phương; Nguyen , Thanh Phong; Pham, Quốc Thy (Tạp Chí Khoa Học Và Công Nghệ Trường Đại Học Bình Dương, 2024)
The digital economy has emerged as a critical factor shaping modern economic structures, driven by rapid technological advancements. Although it has existed since the mid-1990s, the concept and methods of measuring the digital economy remain controversial. This study analyzes various theoretical frameworks and definitions of the digital economy while synthesizing measurement experiences from countries such as China, the United States, and Europe. Differences in measurement approaches have led to inconsistent evaluations of the digital economy’s scale. Based on international experiences, the study proposes a digital economy development framework for Vietnam, consisting of three main components: ICT-based digital economy, Internet and platform-based digital economy, and sector-specific digital economy. This framework emphasizes investment in digital infrastructure, policy reform, and human resource development to foster sustainable growth for Vietnam’s digital economy.